ترجمة معاني الاستعارة في مصحف بروناي دار السلام: دراسة تحليلية تقويمية - الحاجة رفيده بنت الحاج عبدالله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research aims to highlight the strategy used to translate the meanings of verses borrowed in “The Mashaf Brunei Darussalam and Terjemahannya”, and to find out which translations are easier to understand with regards to the interpretation of the verses borrowed from the Qur'an or from the researcher's suggestion. The researcher followed a set of scientific methodologies that dealt with the subject, through the descriptive approach - which is the main key to this research. The researcher described “The Mashaf Brunei Darussalam and Terjemahannya”, by explaining the efforts of the Sultan of Brunei Darussalam in the service of the Qur'an, and then clarified the metaphor in Arabic and Malay. The researcher explained the difficulties related to the translation of the metaphor, described the opinions of the scholars on translation in general and translation of metaphor in particular. Then, through the analytical approach, the researcher analyzed the strategy used in translating the Qur'an into the meanings of the verses that are borrowed to the target language, which is the Malay language, and then evaluate them. In addition to the analyzing and clarifying the results of questionnaires and interviews, the study concluded with a number of results, the most important of them are: The Brunei Darussalam Mushaf used many strategies to translate the meaning of the verse in metaphor, to reproduce the same image in the target language, to replace the image in the source language in the target language, to convert the metaphor into meaning and to delete and to reproduce the same image. The target language with annotation, and replace the image in the source language normally in the target language with annotation and addition. The translation of “The Mushaf Brunei Darussalam and Terjemahannya” for the metaphorical meanings of the metaphor - in the verses selected in the questionnaire - has obtained the second degree of choice. Then the researcher concluded with a set of recommendations.